Oropharyngeal administration of colostrum targeting gut microbiota and metabolites in very preterm infants: protocol for a multicenter randomized controlled trial - Na Wang; Jia Zhang; Zhangbin Yu; Xudong Yan; Lian Zhang; Haibo Peng; Cheng Chen; Rui Li (BMC Pediatrics, 2023)
Abstract Background Oropharyngeal administration of colostrum (OAC) has an immune-stimulating effect on oropharyngeal-associated lymphoid tissue, and can promote the maturation of the gastrointestinal tract. However, how OAC promotes intestinal maturation in preterm infants by altering gut microbiota remains unclear. We aim to assess changes in gut microbiota and metabolites after OAC in very preterm infants. Methods A multicenter, double-blind, randomized controlled trial will be conducted in three large neonatal intensive care units in Shenzhen, China, with preterm infants with gestational age less than 32 weeks at birth and birth weight less than 1500 g. It is estimated that 320 preterm infants will be enrolled in this study within one year. The intervention group will receive oropharyngeal administration of 0.2 ml colostrum every 3 h, starting between the first 48 to 72 h and continued for 5 consecutive days. Following a similar administration scheme, the control group will receive oropharyngeal administration of sterile water. Stool samples will be collected at the first defecation, as well as on the 7th, 14th, 21st and 28th days after birth for analysis of effect of OAC on gut microbiota and metabolites through 16sRNA gene sequencing and liquid chromatography-mass spectrometry. Discussion This proposal advocates for the promotion of OAC as a safe and relatively beneficial protocol in neonatal intensive care units, which may contribute to the establishment of a dominant intestinal flora. Findings of this study may help improve the health outcomes of preterm infants by establishment of targeted gut microbiota in future studies. Trial registration NCT05481866 (registered July 30, 2022 on ClinicalTrials.gov).